Optimization of acceptance test plan for nanosatellites to minimize constellation lifecycle cost - Teo, Kah How (Nanyang Technological University, 2022)
The successful demonstrations of nanosatellite technologies in recent years have brought increased attention to the benefits of nanosatellite constellations. However, it is unclear how the high volume production and testing of nanosatellites should be carried out such that the lifecycle cost of the constellation can be minimized. Burn-in can increase operational reliability and satellite lifetimes, yielding satellites that fail less frequently. However, subsequent replacements are more costly, with replacements also delayed if burn-in factors into the replacement duration. Hence there is a need to study the effects of burn-in on the lifecycle cost of the constellation.